Development of neuro-didactic content aimed at developing the intelligence of younger schoolchildren - Zhumabayeva, Zhazira; Bazarbekova, Rabiga; Nurzhanova, Sazhila; Stambekova, Assel; Kalbergenova, Sholpan B. (Frontiers in Education, 2025)
IntroductionThe increasing integration of neuroscience into education has led to the emergence of neurodidactics, a field that bridges cognitive science, psychology, and pedagogy to enhance student learning outcomes. This study explores the implementation and impact of the elective course “Neurogymnastics,” designed to develop cognitive intelligence, self-regulation, memory, attention, and effective learning strategies among primary school students.MethodsApproved by the City Scientific and Methodological Center for New Educational Technologies, the course was integrated into the 2024–2025 academic curriculum at School-Gymnasium No. 185 (Alatau District, Almaty) and Ozat School (Auezov District, Almaty). The study was conducted over an academic year, incorporating standardized cognitive testing (Wechsler, Raven’s Progressive Matrices, and Cattell’s Culture-Free Intelligence Test) before and after the intervention.FindingsThe research findings indicate enhancements in abilities among students who took part in the Neurogymnastics program when compared to those in the control group. In the group of students there was an increase in verbal intelligence levels; 55% achieved a high proficiency rating on the Wechsler Test as opposed to 40% in the control group. Likewise significant enhancements were noted in reasoning skills; on the Raven’s Test 52% of students from the group demonstrated high performance compared to only 38%, from the control group.DiscussionThe study has established that neurodidactic interventions improve cognitive abilities, executive function, and self-regulation in young learners. The Neurogymnastics course, which is more engaging and interactive than the traditional teaching methods, was found to be more effective in improving students’ interest and learning retention. The control group had moderate cognitive gains, but the experimental group’s better performance was a clear indication that neuroeducation principles should be incorporated into the regular curriculum to help students become more independent, flexible, and critical learners. The novelty of this study lies in the integration of neurogymnastics with gamification and augmented reality, which creates a complete neurodidactic framework that is specifically designed to improve the cognitive development of primary school students.